2024
DOI: 10.1200/go.23.00470
|View full text |Cite
|
Sign up to set email alerts
|

Screening Perspectives: The Role of Colorectal Cancer Awareness in Shaping Attitudes Toward Colonoscopy in Palestine

Mohamedraed Elshami,
Maram Albandak,
Mohammed Alser
et al.

Abstract: PURPOSE To assess colorectal cancer (CRC) awareness and its influence on attitudes toward colonoscopy in Palestine. MATERIALS AND METHODS Convenience sampling was used to recruit Palestinian adults from hospitals, primary health care centers, and public spaces across 11 governorates. To evaluate the awareness of CRC signs/symptoms, risk factors, and mythical causes, the Bowel Cancer Awareness Measure and Cancer Awareness Measure-Mythical Causes Scale were used after translation into Arabic. For each correctly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Consequently, the median score was calculated for each domain. In consistence with previous reporting 9 , displaying a positive attitude was defined as agreeing on at least the median number of questions related to CRC (5 of 11 questions) or colonoscopy (6 of 10 questions). Frequencies and percentages were utilized to describe demonstrating positive attitude toward CRC and colonoscopy, with comparisons between participants from the Gaza Strip versus the West Bank and Jerusalem performed using Pearson’s Chi-Square test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the median score was calculated for each domain. In consistence with previous reporting 9 , displaying a positive attitude was defined as agreeing on at least the median number of questions related to CRC (5 of 11 questions) or colonoscopy (6 of 10 questions). Frequencies and percentages were utilized to describe demonstrating positive attitude toward CRC and colonoscopy, with comparisons between participants from the Gaza Strip versus the West Bank and Jerusalem performed using Pearson’s Chi-Square test.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies from Palestine found that awareness levels of CRC risk factors and signs/symptoms were low with 60% of the population showing poor or fair awareness 7 , 8 . Interestingly, another study from Palestine looking into the role of CRC awareness in relation to attitudes toward colonoscopy showed that better awareness of CRC signs/symptoms and risk factors was associated with more positive attitudes toward colonoscopy as a screening modality 9 .…”
Section: Introductionmentioning
confidence: 99%